Pengaruh Pemberian Abu Serbuk Gergaji dan Pupuk Guano terhadap Pertumbuhan dan Produksi Tanaman Cabai (Capsicum annuum L.) - Rulianto, Jihan; Yetti, Husna; Anom, Edison (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aim to determine the effect of giving sawdust ash and guano fertilizer between both of it on chilli (Capsicum annuum L.) growth and production as well as to find out the best dose. This research has been conducted at Experimental Garden, University of Riau, Tampan District, lasted from April to September 2013. Research was arranged experimentally using Completely Randomized Block Design (CRBD) with 2 factor, first is giving sawdust ash and the second one is fertilizing with guano fertilizer which is each of it consist by 3 replication. First factor; A0, A1, A2 and A3 (0, 5, 10 and 15 ton/ha), second factor; G0, G1 and G2 (0, 60 and 120 g/plot). Oberserved parameters are plant height, flowering date, harvesting date, total weight per plant, total weight per plot, fruit length, fruit girth and number sampling fruit. Data analyzed using the F test and Duncan New’s Multiple Range Test (DNMRT) 5% level. Result shows that the combination of giving sawdust ash and Guano Fertilizer reveal non significantly different to all of the parameters, but by giving sawdust ash and guano fertilizer reveal significantly different to the plant height. Keywords: sawdust ash, guano fertilizer and chilli (Capsicum annum L.)